Evaluation of JQ1 Combined With Docetaxel for the Treatment of Prostate Cancer Cells in 2D- and 3D-Culture Systems - Xu, Yipeng; Pachnikova, Gabriela; Przybilla, Dorothea; Schäfer, Reinhold; Cui, Yingying; Zhou, Dan; Chen, Zihao; Zhao, An; Keilholz, Ulrich (Frontiers in Pharmacology, 2022)
Introduction: Prostate cancer (PCa) is dependent on coupled androgen-androgen receptor (AR) signaling for growth and progression. Significant efforts have been made in this research field, as hormonal therapies have greatly improved the survival of patients with metastatic PCa (mPCa). The drug treatment agent JQ1, which potently abrogates bromodomain 4 (BRD4) localization to the AR target loci and therefore significantly impairs AR-mediated gene transcription, is a potent therapeutic option for patients with advanced PCa. In this study, we aimed to investigate the inhibitory effect of JQ1 combined with docetaxel on PCa cells in vitro for the first time. Furthermore, the 3D spheroid culture system was modeled to more accurately simulate the response of PCa cells to drugs. Methods: We established and measured 3D LNCaP spheroids in vitro in order to evaluate the susceptibility of 2D- and 3D-cultured LNCaP cells exposed to the same anti-cancer drug. Results: We demonstrated that JQ1 was an effective drug for promoting cell inhibition after docetaxel treatment in 2D- and 3D- cultured LNCaP cells. Inhibition of 3D cultured formation in the combined treatment group was significantly higher than that in docetaxel or JQ1 alone. Under the same conditions of drug solubility, the drug resistance of 3D spheroids was significantly higher than that of 2D cells. Moreover, dmax and lg volume were suitable parameters for LNCaP cells/spheroid size displaying and evaluating cell viability. Conclusions: 3D cultured spheroids of PCa are an effective tool for studying PCa drug trials. JQ1 combined with docetaxel may be an effective treatment for advanced PCa. This combination therapy strategy deserves further evaluation in clinical trials.